Pengaruh tekanan eksternal, ketidakpastian lingkungan dan komitmen manajemen terhadap penerapan transparansi pelaporan keuangan (studi pada satuan kerja perangkat daerah pemerintah kabupaten rokan hilir) - Sihaloho, Johannes; Satriawan, Raja Adri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study examined the effects of external pressure, environmental uncertainly and management commitment on transparency of financial reporting.The sample of this studied consist of 42 SKPD in Rokan Hilir. Analytical techniques used to perform the hypothesis testing is purposive sampling. Data are analyzed using multiple regression analysis using SPSS (Statistical Product and Service Solution) 17 version.The results showed that the external pressure and management commitment had a effect to transparency of financial reporting. But environmental uncertainly had not effect to transparency of financial reporting. External pressure showed coefficient 0,379 with the signification values 0,016. This the decision made is to accept hypothesis H1. Environmental uncertainly showed coefficient 0,105 with the signification values 0,406. This the decision made was to reject hypothesis H2. And the management commitment showed coefficient 0,353 with the signification values 0,019. This the decision made is to accept hypothesis H3.Keywords : transparency of financial reporting, external pressure, environmental uncertainly and management commitment.